PENGARUH KEWAJARAN HARGA, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN - Mustafa, Rifqi; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2022)
The situation during the Covid-19 pandemic has killed many industrial sectors, one of the affected industrial sectors is the tourism sector in Bali, so that the form of trade businesses that sell used hotel and restaurant goods become more developed by taking advantage of the situation. In general, people will take the decision to buy second-hand goods in order to meet their needs after choosing used goods at an affordable price, good quality, and a location where shopping for used goods is easy to reach, because these factors can influence a customer's purchasing decisions. The purpose of this research is to explain the effect of fairness of price, product quality, and location on the decision to purchase used goods in bedugul ex hotel &resto shop. The population used is customers who have purchased products from Toko Bedugul Ex Hotel &Resto. The sample used was as many as 65 people. The analysis technique used is multiple regression analysis. The results of the analysis showed that the fairness of the price, product quality, and location had a positive and significant effect on the purchase decision of Toko Bedugul ex hotel &resto in Denpasar City. This means that the better the perception of fairness of consumer prices on products in Toko Bedugul ex hotel &resto, the higher the quality of products and the more strategic the location of Toko Bedugul ex hotel &resto, it will affect the purchase decisions that are increasing. Keywords: fairness of price, product quality, location, purchasing decision